Pengembangan Media Pembelajaran Ular Tangga Materi Sistem Peredaran Darah untuk Meningkatkan Hasil Belajar Peserta Didik - Luthfi Rahayu Ningsih; Ismi Yunita Harun; Vina Rahmadiana; Mieke Miarsyah; Rizhal Hendi (Jurnal Pendidikan Biologi, 2020)
This research aims to developing snake ladder learning media in circulatory system material and knowing the effectiveness of snake ladder learning media on learning outcomes of science. This study uses Research and Development according to Borg and Gall and experimental tests with the design of pretest posttest control group design. Data obtained in the form of quantitative data and qualitative data. The results of validation by material experts were 85% (very feasible), by media experts at 81% (very feasible), and by linguists expert 77% (feasible), with an average overall score of 81% (very feasible). The results show that the snake ladder learning media on the circulatory system material is very feasible to be used in learning, as well as the snake ladder learning media on the circulatory system material effectively improves student learning outcomes.